Education and the Journey to the Core: Path-dependence or Leapfrogging? - Aashish Mehta; Jesus Felipe (Asian Development Bank (ADB), 2014)
We study changes in 130 countries' indices of revealed comparative advantage for 1,240 products between 1995 and 2010, to answer: (i) whether export diversification is path-dependent, and whether it is more difficult to diversify into more sophisticated products; and (ii) whether education helps reduce path-dependence, or to develop comparative advantage in sophisticated products. We develop a regression framework that includes a measure of how distant a target product is from those products a country exports with comparative advantage, and measures of product sophistication. We combine these with estimates of the quality and quantity of education that a country's workforce possesses. We find, first, that, over this period, the development of comparative advantage is a path-dependent process - stepping stones products must usually be developed to approach new products. Second, there is strong evidence consistent with the view that education helps reduce this path-dependence by facilitating more rapid incremental movement across the stepping stones of industrial development. Results also indicate that education quality matters more than education quantity, and that high-quality basic education matters for export diversification. Our framework also allows us to test whether leapfrogging into what we refer to as core products is possible and conclude that this is very unlikely.
hdl:11540/1974
Keywords: I25; O11; O14; 330; core; density; diversification; education; leapfrogging; path-dependence; periphery; revealed comparative advantage